KETERKAITAN DANA DESA TERHADAP KEMISKINAN DI KABUPATEN LOMBOK UTARA - Adi Artino; Bambang Juanda; Sri Mulatsih (Diponegoro University, 2019)
Poverty is one of the indicator of development performance, in terms of community welfare. Cause of poverty due to uneven distribution of income and inequality of development. Village funding programs for each village provide positive implications for community welfare. This study aims to see the relationship of village funds to poverty in North Lombok Regency. The method used is geographically weighted regression (GWR). Village funds can reduce poverty in each village in North Lombok Regency, but it does not have a significant effect in reducing poverty because the resulting model is still influenced by other variables outside the model. The variable coefficient of the number of bachelor and paddy fields in each village can reduce poverty and some can increase poverty. So there is a need for policy variation to reduce poverty in each village.